Mesogenic azomethine esters with different end groups: Synthesis and thermotropic properties - Ha, Sie-Tiong; Ng, Mei-Yoke; Subramaniam, R.T.; Ito, M.M.; Saito, A.; Watanabe, M.; Lee, Siew-Ling; Bonde, N.L. (Academic Journals, 2010)
Series of elongated azomethine esters containing two aromatic rings with stearoyl moiety as one of the terminal carbon chain and various substituents X (where X = H, F, Cl, Br, OCH(3), CH(3) and C(2)H(5)) at the other end of molecule have been isolated and their structures were proposed via physical measurement. The mesomorphic properties of these compounds were investigated via differential scanning calorimetry and polarizing optical microscopy. The thermal data indicate that compounds with fluoro, chloro, bromo and methoxy substituents exhibit mesomorphic properties and the rest of the compounds are non mesogenic materials. While compound with X = OCH(3), show nematic phase, the compounds containing halogen F, Cl and Br are smectogenic in nature. The presence of a lateral hydroxyl group has been claimed to contribute to the enhanced molecular ordering, leading to a higher clearing temperature.